A Model for Assessing Business Intelligence level of Enterprise Systems - SaeedRouhan Rouhani; AhadZare Ravasan (مطالعات مدیریت کسب و کار هوشمند, 2013)
Most organizations still experience a lack of Business Intelligence (BI) in their decision making processes when implementing enterprise systems, such as Enterprise Resource Planning (ERP), Customer Relationship Management (CRM), and Supply Chain Management (SCM). Consequently, a model and techniques to evaluate and assess the intelligence-level of enterprise systems can improve decision support. This paper proposes an expert tool to evaluate the BI competencies of enterprise systems, and combines a comprehensive review of recent literature with statistical methods for factor analysis. A statistical analysis has identified six factors for the evaluation model: ‘‘Analytical and Intelligent Decision-support’’, ‘‘Providing Related Experimentation and Integration with Environmental Information’’, ‘‘Optimization and Recommended Model’’, ‘‘Reasoning’’, ‘‘Enhanced Decision-making Tools’’, and finally, ‘‘Stakeholder Satisfaction’’.  Enterprises can use this approach to evaluate, select, and buy software and systems that provide better decision support for their organizational environment, enabling them to achieve competitive advantage.